MicroRNA‐193a‐5p exerts a tumor suppressor role in glioblastoma via modulating NOVA1. Issue 4 (10th October 2018) - Jin, Lingjiang; Li, Huiyong; Wang, Junyou; Lin, Da; Yin, Kang; Lin, Ligang; Lin, Zheng; Lin, Gaojun; Wang, Hui; Ying, Xiaowei; Wang, Lisong; Zhang, Yongqiang; et al.
Abstract: Background and Objectives: Glioblastoma (GBM) is the most common and lethal of intracranial tumors, which is characterized by extensive proliferation and the diffused invasion of tumor cells. MicroRNA‐193a‐5p (miR‐193a‐5p) have been demonstrated previously as a functional suppressor in the development and progression of various cancers. The current study aimed to investigate whether miR‐193a‐5p influences cell proliferation and migration through the mitogen‐activated protein kinase/extracellular signal‐regulated kinase signaling pathway by targeting neuro‐oncological ventral antigen 1 (NOVA1) in glioblastoma. Materials and Methods: The miR‐193a‐5p expression was detected by quantitative real‐time polymerase chain reaction assay in GBM tissues and cell lines. Cell Counting Kit‐8 assay, colony formation analysis, wound‐healing, and transwell invasion assays were performed to evaluate cell proliferation, colony formation, migration, and invasion, respectively. Western blot analysis and luciferase reporter gene assay were performed to verify the downstream target gene of miR‐193a‐5p. Results: The expression of miR‐193a‐5p was significantly downregulated in GBM tissues and cell lines. Kaplan‐Meier analysis showed that patients with low miR‐193a‐5p expression had a shorter disease‐free survival ( P < 0.05). Functionally, miR‐193a‐5p overexpression dramatically suppressed the proliferation, colony formation, migration, and invasion in glioma cells. Bioinformatics prediction and a luciferase assay confirmed that NOVA1 was a direct functional target of miR‐193a‐5p. Moreover, ectopic expression of NOVA1 could partially reverse the inhibitory effects of miR‐193a‐5p on glioma cell proliferation, colony formation, migration, and invasion. NOVA1 overexpression abrogated the inhibitory effect of miR‐193a‐5p on the PTEN/PI3k/AKT pathway. Conclusion: Taken together, our findings suggested that miR‐193a‐5p functions as a tumor suppressor in glioma cells by directly targeting NOVA1. Abstract : Taken together, based on the evidence obtained from the current study, we draw to the conclusion that miR‐193a‐5p functions as a tumor suppressor in glioma cells by directly targeting NOVA1